In Situ Synthesis of MOF‐74 Family for High Areal Energy Density of Aqueous Nickel–Zinc Batteries - Chen, Tingting; Wang, Fanfan; Cao, Shuai; Bai, Yang; Zheng, Shasha; Li, Wenting; Zhang, Songtao; Hu, Shu‐Xian; Pang, Huan (Advanced materials (Weinheim), 2022)
Limited by single metal active sites and low electrical conductivity, designing nickel‐based metal–organic framework (MOF) materials with high capacity and high energy density remains a challenge. Herein, a series of bi/multimetallic MOF‐74 family materials in situ grown on carbon cloth (CC) by doping Mx+ ions in Ni‐MOF‐74 is fabricated: NiM‐MOF@CC (M = Mn2+, Co2+, Cu2+, Zn2+, Al3+, Fe3+), and NiCoM‐MOF@CC (M = Mn2+, Zn2+, Al3+, Fe3+). The type and ratio of doping metal ions can be adjusted while the original topology is preserved. Different metal ions are confirmed by X‐ray absorption fine structure (XAFS). Furthermore, these Ni‐based MOF electrodes are directly utilized as cathodes for aqueous nickel–zinc batteries (NZBs). Among all the as‐prepared electrodes, NiCo‐MOF@CC‐3 (NCM@CC‐3), with an optimized Co/Ni ratio of 1:1, exhibits the best electrical conductivity, which is according to the density functional theory (DFT) theoretical calculations. The NCM@CC‐3//Zn@CC battery achieves a high specific capacity of 1.77 mAh cm–2, a high areal energy density of 2.97 mWh cm–2, and high cycling stability of 83% capacity retention rate after 6000 cycles. The synthetic strategy based on the coordination effect of metal ions and the concept of binder‐free electrodes provide a new direction for the synthesis of high‐performance materials in the energy‐storage field. A series of nickel‐based metal–organic frameworks (MOFs) (bi/multimetallic MOF‐74 family) in situ grown on carbon cloth is fabricated in application of aqueous Ni–Zn batteries. The synthetic strategy based on the coordination effect of metal ions and the concept of binder‐free electrodes provide a new direction for the synthesis of high‐performance materials in the energy‐storage field.